RANCANG BANGUN SISTEM PEMANEN ENERGI ANGIN EXHAUST FAN DENGAN TURBIN ANGIN ARCHIMEDES SUMBU HORIZONTAL - I Made Agus Artha Putra; Cokorde Gede Indra Partha; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2021)
Wind ienergy iis iwidely iused ito ireplace ifossil ifuels iwith ivarious itechnologies, ibut iutilizationiby iusing iArchimedes iwind iturbines iis istill irarely ifound. iIn ithis ipaper, iresearch iis iconducted ionithe iimplementation iof ithe iArchimedes iwind iturbine ion ithe iexhaust ifan ito ibe iable ito iutilize itheiexhaust ienergy iproduced. iThe itest iresults ishow ithat ithe imaximum ipower ican ibe iproducedireaches i1.91 iW iat ia idistance iof i10 icm, ibut ithe ipower iproduced iis ionly i0.37 iW. iThe ioptimalidistance ito iplace ithe iturbine ito iharvest ienergy iis iat ia idistance iof i30 icm ibecause iat ithat idistanceithe iArchimedes iwind iturbine iis iable ito iharvest ienergy iof i1.54 iW.